THE EFFECTS OF AMETHYST Datura metel (LINN, 1753) LEAVES EXTRACT AS AN ANESTHETIC AGENT ON HAEMATOLOGICAL CONDITION OF TILAPIA Oreochromis niloticus (LINN,1758) FRY - Revita Syefti Palmi; Indra Gumay Yudha; Wardiyanto Wardiyanto (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2019)
Anesthetic method is an important component to support the activities of transporting live fish from one place to another for a long period of time. Cost efficiency and effectiveness of anesthetic ingredients that not cause residues in fish are factors to beconsidered as an anesthetic. Aim of this research is to study the effect of subletal concentration of amethyst leaf extract on the hematological conditions of tilapia fry after transporting on wet transportation systems. The research procedure was through the amethyst leaf extract toxicity test series (LC50-96 hours) to determine its sublethal concentration by 20% (0,297 ml/l), 30% (0,445 ml/l) and 40% (0,594 ml/l) of the LC50 value. The measured parameters are clinical symptoms, period of fainting and conscious recovery, hematological analysis, survival rate, and water quality. The results showed the concentration of amethyst leaf extract had an effect (P<0,05) on the period of fainting and the hematological component after transportation simulation. Results of water quality measurement showed the parameters of pH at 6 and ammonia 0,04 mg/l are not at the optimum value when fish transportation occur. The recommended concentration of amethyst leaf extract for use as an anesthetic agent is 0,445 ml/l